S46 The Risk of Obstructive Sleep Apnoea is Significantly Higher in Patients with Chronic Kidney Disease - a Study from a Single UK Renal Centre. (19th November 2012) - Seccombe, AW; Ferguson, P; Baharani, J
Abstract : Introduction and Objectives: Along with known associations with coronary heart disease, heart failure and stroke, there is increasing evidence to demonstrate a link between obstructive sleep apnoea (OSA) and chronic kidney disease (CKD). There is also growing evidence to suggest that intensive treatment of CKD can improve or even eliminate symptoms related to OSA. So far though, there is no evidence to support the association between OSA and CKD in a UK population. Our study aimed to quantify the risk of OSA in different severities of CKD for the first time in the UK Our secondary aim was to look for factors that increased or decreased this risk, including medications. Methods: Using the renal database, 60 patients each at CKD stage 3b, 4 and 5, haemodialysis patients and renal transplant patients were identified, matched for age and sex and sent the Berlin questionnaire and a lifestyle questionnaire. The Berlin questionnaire was used to stratify patients into high-risk and low-risk groups for OSA. We used the lifestyle questionnaire along with up-to-date laboratory investigations to investigate variables that altered this risk within our sample. Results: Of the 300 patients who were contacted, 111 (37%) responded. Of the 111 respondents, 78 (70.2%) were found to be at high-risk of OSA. This significant increase in risk was seen in all severities of CKD that were examined including in CKD 3b (80.8%). In contrast to the general population, where OSA is more common in men, our study found that 77.1% of women were at high-risk of OSA compared to 65.1% of men. We also found that renin-angiotensin system inhibitors (RASI) were associated with a reduced risk of OSA with 66.1% of users being at high risk compared to 74.5% of non-users. Conclusions: Our study is the first to demonstrate the link between OSA and CKD in a UK population, a link that holds for milder forms of CKD. We noted that RASI use helped to reduce the risk of OSA, thus identifying a possible medical treatment for OSA in patients with CKD. Further study will clarify the importance of this treatment.